Analisis Kualitas Layanan Sistem Informasi Aplikasi Access KAI sebagai E-Government dengan E-GovQual - Syahreza, M. Ryan; Sulaksono, Aditya Galih (Universitas Batanghari Jambi, 2024)
This research evaluates the service quality of the Access By KAI application developed by PT. KAI using the E-GovQual method. This application provides various features such as ticket booking, travel information, and additional services. With a survey of users in Malang and analysis using SPSS. The research results show that the Access By KAI application has good quality, but there are several areas that require improvement, such as effectiveness and service.